Prevalencia de edentulismo total y parcial en adultos mayores de un establecimiento de salud del minsa Iquitos 2024 - Vásquez Maslucan,Luz Juliana (2024)
The general objective of this research was to determine the prevalence of total and partial edentulism in older adults from a MINSA health facility, Iquitos – 2024. The sample was made up of 216 older adults from the I-4 “San Juan de Miraflores” health facility. ” from the city of Iquitos. The results showed that 47.7% of older adults presented total edentulism, and 52.3% did not present it. 68.1% of older adults presented partial edentulism, and 31.9% did not. It is concluded that the prevalence of total edentulism in older adults in a MINSA facility in Iquitos is low. Likewise, the prevalence of partial edentulism in older adults in a MINSA facility in Iquitos is high.